ANALISIS SISTEM UTILITAS PADA GEDUNG KEAHLIAN TEKNIK ALAT BERAT SMK NEGERI 1 SINGOSARI - Astrela Regina Shirley Uma; Eko Suwarno; ⁠Atdjeng Chrisnudin; Atsiil Putra Utama; Aulia Rahma Efendi; Tee Tze Kiong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocational education buildings require more complex utility systems compared to general education buildings because learning activities focus on practical work using machines and equipment. In the Heavy Equipment Engineering Building at SMK Negeri 1 Singosari, lighting and ventilation systems play an important role in supporting safety, comfort, and effectiveness during practical activities. The problem addressed in this study is the condition of the utility systems, particularly lighting and ventilation, and the constraints found in the building. This study aims to analyze and identify the utility systems in the Heavy Equipment Engineering Building of SMK Negeri 1 Singosari, identify existing problems and constraints, and provide a basis for facility development. The research method used was a descriptive method with a field observation approach. Data were collected through direct observation and documentation of lighting and ventilation systems on the first and second floors of the building. The results showed that the lighting system on both floors utilized a combination of natural and artificial lighting; however, several areas on the first floor still had uneven light intensity, especially during cloudy or rainy conditions. The ventilation system on the first floor used natural ventilation and exhaust fans, while the second floor used mechanical ventilation in the form of air conditioners and fans, which were effective in maintaining thermal comfort. Overall, the utility system in the building has supported practical learning activities, but further maintenance and development are still required to improve comfort and energy efficiency